Using Cognitive Coaching to Build School Leadership Capacity: A Case Study in Alberta - Rogers, W. Todd; Hauserman, Cal P.; Skytt, Jacqueline (Canadian Journal of Education/Revue canadienne de l'éducation, 2016)
The impact of Cognitive Coaching included as part of the Leader2Leader (L2L) Leadership Pilot Program for beginning principals in Alberta, Canada, was evaluated in the present study. Fifteen qualified principals (coaches) and 23 new principals completed the L2L Pilot Program that took place over 18 months. Questionnaires for coaches and new principals were used to obtain reactions to the Cognitive Coaching component. The findings suggest that the L2L Leadership Program can help develop a network of reflective, self-reliant school principals. Recommendations for improving the Cognitive Coaching component of the L2L Leadership Program are provided.